2002
DOI: 10.1016/s1074-7613(02)00368-0
|View full text |Cite
|
Sign up to set email alerts
|

Herpesviral Protein Targets a Cellular WD Repeat Endosomal Protein to Downregulate T Lymphocyte Receptor Expression

Abstract: Herpesvirus saimiri Tip associates with Lck and downregulates Lck signal transduction. Here we demonstrate that Tip targets a lysosomal protein p80, which consists of an N-terminal WD repeat domain and a C-terminal coiled-coil domain. Interaction of Tip with p80 facilitated lysosomal vesicle formation and subsequent recruitment of Lck into the lysosomes for degradation. Consequently, Tip interactions with Lck and p80 result in downregulation of T cell receptor (TCR) and CD4 surface expression. Remarkably, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
78
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 29 publications
8
78
0
Order By: Relevance
“…Likewise, HIV-infected T cells had reduced ability to from synapses with APCs. In T cells infected with HSV, Lck was targeted to lysosomes, where it underwent degradation (34). As a result, the amount of Lck at the plasma membrane was substantially reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, HIV-infected T cells had reduced ability to from synapses with APCs. In T cells infected with HSV, Lck was targeted to lysosomes, where it underwent degradation (34). As a result, the amount of Lck at the plasma membrane was substantially reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Like T cells transformed with the parental HVS C488 (28), they displayed typical surface markers of mature T cells. It has been reported that overexpression of Tip in T-cell lines results in a downmodulation of CD3 and CD4 surface expression (57), which was more pronounced in Tip-Y114S (32,58). In our hands, HVS-transformed cells expressing the HVS oncogene tip from the viral promoter do not show such a dramatic effect; instead, they showed only a modestly lower surface expression of CD3 in C488-Y114F-transformed cells compared to HVS-C488-transformed cells and normal expression of CD4 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 would have been an attractive candidate, but it is excluded by this study. Numerous other proteins not yet characterized have been reported to bind Tip (58,66). Of these proteins, there may be interesting candidates interfering with cellular signaling pathways contributing to transformation.…”
Section: Discussionmentioning
confidence: 99%
“…ORF14 protein, a homolog of MMTV vSag, is detected primarily during lytic replication and induces the polyclonal proliferation of CD4-positive T cells through an interaction with MHC class II-TCR molecules (60). Tip, which is expressed primarily during viral latency, interacts with Lck tyrosine kinase and p80 endosomal protein and thus interferes with early events in the TCR signal transduction pathway and induces a rapid endocytosis of the TCR complex (39,40). Finally, ORF5, which is expressed primarily during viral replication cycle but not during the viral latent cycle (unpublished results), interacts with cellular SH2-containing proteins, which results in the strong augmentation of TCR signal transduction.…”
Section: Discussionmentioning
confidence: 97%
“…As a lipid raft resident protein, Tip interacts with the SH3 domain of Lck tyrosine kinase, and this interaction interferes with early events in the TCR signal transduction pathway (3,27,35). Furthermore, Tip interacts with a novel cellular endosomal protein, p80, which contains an amino-terminal WD repeat domain and a carboxy-terminal coiled-coil domain (39,40). Interaction of Tip with p80 facilitates endosomal vesicle formation and subsequent recruitment of Lck and TCR into the endosomes for degradation.…”
mentioning
confidence: 99%